Effect of annealing on the structural, morphological, optical, magnetic, and dielectric properties of nickel-doped cobalt nanoferrites for electronic applications - Md Shihabun Sakib; Md Naimur Rahman; Md Alamgir Hossain; Md Rashedur Rahman (Physics Open)
Nanocrystalline powders of nickel-substituted cobalt ferrite were synthesized using the chemical co-precipitation method with ammonia solution as the precipitating agent, maintaining a nickel-to-iron mole ratio of 1:3. The effects of annealing at 600 °C, 650 °C, 700 °C, and 750 °C on the structural, morphological, optical, magnetic, and dielectric properties of the samples were evaluated using X-ray diffraction (XRD), scanning electron microscopy (SEM), a UV–vis–NIR spectrophotometer (UV), a vibrating sample magnetometer (VSM), and an impedance analyzer. X-ray diffraction analysis confirmed the f.c.c spinel structure with an Fd3m symmetric space group, and crystallite sizes increased from 15.96 to 19.11 nm with higher annealing temperatures. SEM revealed nanoparticle sizes of 362.14–444.88 nm, each comprising 22–23 crystals. UV spectroscopy indicated semiconductor behavior with band gaps ranging from 1.86 to 2.15 eV. Dielectric constant and losses decreased with higher annealing temperature and frequency. Annealing affected interionic bond lengths, distances, and angles, resulting in an increase in coercivity from 77.15 to 117.70 Oe, while saturation magnetization decreased from 9.15 to 5.32 emu/g, indicating the soft magnetic properties of CNSF nanoparticles. The Curie temperature dropped from 551.29 °C to 379.55 °C as temperature increased. The experimental results align with reported values, showing that higher annealing temperatures provide optimal structural, morphological, and magnetic properties, while lower temperatures favor optical and dielectric properties in CNSF nanoparticles.